A spinal manipulative therapy altered brain activity in patients with lumbar disc herniation: A resting-state functional magnetic resonance imaging study - Wen, Ya; Chen, Xiao-Min; Jin, Xin; Ling, Dong-Ya; Chen, Shao; Huang, Qin; Kong, Ning; Chai, Jin-Er; Wang, Qing; Xu, Mao-Sheng; Du, Hong-Gen (Frontiers in Neuroscience, 2022)
Purpose: Lumbar disc herniation (LDH) is one of the leading causes of low-back pain and results in a series of clinical symptoms, including pain, reflex loss, and muscle weakness. Spinal manipulative therapy (SMT) can relieve pain and promote internal and external stabilization of the lumbar spine. In this study, we investigated whether the brain alterations of LDH patients with SMT were frequency-dependent based on the calculation of Amplitude of Low-Frequency Fluctuations (ALFF) and fractional ALFF (fALFF). Further, we established a cohort of LDH patients to evaluate the contribution of SMT treatments to brain functional reorganization. Methods: A total of 55 participants, including 27 LDH patients and 28 health controls (HCs), were collected. All LDH patients underwent two fMRI scans (before SMT and after the sixth SMT session). To represent LDH-related brain oscillatory activities, we calculated the ALFF and fALFF in the conventional band (0.01–0.08 Hz), the slow-4 band (0.027–0.073 Hz), and the slow-5 band (0.01–0.027 Hz). Moreover, we extracted ALFF and fALFF values in clusters with significant differences to evaluate the SMT effect. Results: Compared with HCs, the LDH patients before SMT (LDH-pre) exhibited increased fALFF in right lingual gyri in the conventional band, and showed increased fALFF in left Cerebelum_Crus1 in the slow-4 band. We further examined the abnormal brain activities changes before and after the SMT intervention. The ALFF and fALFF values of LDH-pre group were higher than those of the HCs and LDH-pos groups. After SMT, the increased ALFF and fALFF values were suppressed for patients in conventional band and slow-4 band. Conclusions: The present study characterized the altered regional patterns in spontaneous neural activity in patients with LDH. Meanwhile, SMT is an effective treatment of LDH, and we supposed that it might have been involved in modulating dysfunctional brain regions which are important for the processing of pain. The findings of the current study may provide new insights to understand pathological mechanism of LDH.